Contribution to the knowledge of the genus Fossia Volynkin, Ivanova & S.-Y. Huang, 2019 (Lepidoptera: Erebidae: Arctiinae: Lithosiini) from China with description of a new subspecies - Huang, Chu-Yang; Volynkin, Anton V.; Zhu, Li-Juan; Wang, Min; Huang, Si-Yao (Zootaxa, 2021)
New information on the genus Fossia Volynkin, Ivanova & S.-Y. Huang, 2019 from China is provided. A new subspecies of F. bachma (Volynkin & Černý, 2018) is described from Hainan, southern China: Fossia bachma hainanensis S.-Y. Huang & Volynkin ssp. nov., which is confirmed by morphological and molecular evidences. Fossia punicea (Moore, 1878) has been formally recorded from Yunnan, southwestern China, where it is represented by the subspecies F. punicea kachina (Volynkin & Černý, 2018). Adults and genitalia of the aforementioned taxa are illustrated.